Modular assembly of a single phase inverter based on integrated functional block - Castellazzi, Alberto; Solomon, Adane Kassa; Delmonte, N.; Cova, P. (IEEE, 2017)
This paper presents an original modular plug-in type assembly approach for a single phase-inverter. The main focus here is, indicatively, on the power range 1-20 kW, but the methodology can be transferred to higher power levels, too. At the core of the inverter lies a power-dense double-sided-cooled half-bridge power switch architecture with integrated cooler, which is interconnected to filter elements, gate-driver and control circuitry by means of compact flat connectors. The integration exercise targets, on the one hand, the optimization of the power switch performance and reliability, as well as the reduction of circuit parasitic elements; on the other, the production of a system compatible with maintenance and repairing, featuring minimized impact of single component failure on the system maintenance and repair cost and thus on its availability. Preliminary experimental tests demonstrate the nominal functionality of the inverter.